Durability of engineering structures design, repair and maintenance - Bijen, Jan (CRC ; Woodhead, 2003)
Structures often deteriorate because not enough attention is given during the design stage. Designing for durability is often left to the structural designer or architect who does not have the necessary skills, and the result is all too often failure, incurring high maintenance and repair costs. Knowledge of the long-term behaviour of materials, building components and structures is the basis for avoiding these costs. This book is aimed at degree students in civil engineering, engineers, architects, contractors, plant managers, maintenance managers and inspection engineers.
Keywords: Strength of materials.; Structural engineering.; Materials -- Deterioration.; Building materials -- Service life.; elektronické knihy; electronic books